The Future of the Arab Spring in Postnormal Times (American Journal of Islam and Society, 2013)
To understand how the Arab Spring may evolve over the coming years, wehave to understand its specific context. The “revolutions” across the MiddleEast are not just a product of discontent and fury against dictatorships; afterall, the Arabs have been raging against their rulers for well over half a century.The Arab Spring is also a creation of a particular period of time, a time inwhich globalization, interconnection, and instant communication are the norm,and authority and political legitimacy are in flux. It is a period of uncertainty,ambiguity, chaotic behavior, and rapid change that I have elsewhere describedas “postnormal times.”1Moreover, as Nader Hashemi has observed, “the ArabSpring is not a single event but rather a long-term process of political change.Its precipitating factors were both political and economic; and while historyhas yet to render its ultimate judgment, fundamental questions remain abouthow best to understand the nature, character, and trajectory of Arab revolts.”2I contend that we need to grasp the context of postnormal times, which servedas a catalyst for the Arab revolts and within which the long-term process ofpolitical transformation is taking place, to comprehend the dynamics of theArab Spring and anticipate its trajectory.To appreciate the reality of contemporary times, it is important to realizethat the problems of the Arab state, indeed the problems of all societies, nationalas well as international, are complex. The politics of a democracy, thequestions of economic reforms, the hopes and aspirations of a diverse andpluralistic society, the stubbornness of entrenched institutions such as the policeand the military, are all complex issues that do not have simple or straightforwardanswers. Complexity is enhanced by the fact that all such problems ...